Propuesta de un plan de negocios para la creación de una empresa de herraduras para caballo obtenidas a partir de llantas usadas en el municipio de Supatá Cundinamarca. (2021)
The purpose of my work is to get the viability and evaluation how to generate a business to make and commercialize horseshoes with used tires, doing a previous evaluation of costs, requirements of fabrication, market segment, size of the market, and data of market competition,. etc.